Analysis of LINC00472 as a biomarker of osteoarthritis and its clinical value - Zhiduo Li,; Weijun Zhang, (Archives of Rheumatology, 2024)
Objectives: This study aimed to investigate the effect of LINC00472 in osteoarthritis (OA) and its molecular mechanism. Patients and methods: This prospective study was conducted with 110 patients (59 females, 51 males; mean age: 58.6±10.3 years; range, 37 to 79 year) with OA and 101 healthy controls (58 females, 43 males; mean age: 60.6±10.3 years; range, 35 to 78 years) between June 2020 and November 2022. First, we measured LINC00472 levels in OA patients using RT-qPCR (real-time quantitative reverse transcription polymerase chain reaction). Afterward, we treated human chondrocytes with interleukin (IL)-1β, which aimed to construct an OA cellular model to explore the function of LINC00472 in OA. Messenger RNA levels were detected by RT-qPCR. Apoptosis was measured by flow cytometry. Cell viability was measured by CCK-8 (cell counting kit-8) assay. Enzyme-linked immunosorbent assay was used to detect inflammatory factor levels. Finally, we verified the targeting of miR-361-5p with LINC00472 and MECP2 by luciferase assay and RNA immunoprecipitation. Results: In OA patients and OA cells, LINC00472 and MECP2 levels were increased, and miR-361-5p levels were decreased. LINC00472 levels were negatively correlated with miR-361-5p levels and positively correlated with MECP2 levels. In human chondrocytes, LINC00472 knockdown inhibited apoptosis, cellular inflammation, and extracellular matrix degradation. However, miR-361-5p inhibitor reversed these effects. In addition, LINC00472 knockdown downregulated MECP2 levels, and miR-361-5p inhibitor reversed the effect. Conclusion: LINC00472 is involved in chondrocyte apoptosis, extracellular matrix degradation, and cellular inflammation in OA through the miR-361-5p/MECP2 axis. LINC00472 may regulate OA development by increasing MECP2 expression through sponged miR-361-5p and may be a new target for OA diagnosis and treatment.